2018
DOI: 10.1080/02786826.2018.1432028
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of aerosolized surrogates of Bacillus anthracis spores by combustion products of aluminum- and magnesium-based reactive materials: Effect of exposure time

Abstract: Targeting bioweapon facilities may release biothreat agents into the atmosphere. Bacterial spores such as Bacillus anthracis (Ba) escaping from direct exposure to the fireball potentially represent a high health risk. To mitigate it, reactive materials with biocidal properties are being developed. Aluminum-based iodine-containing compositions (e.g., Al¢I 2 and Al¢B¢I 2 ) have been shown to inactivate aerosolized simulants of Ba effectively, i.e., by factors exceeding 10 4 when the spores are exposed to their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…As-received Mg unexpectedly had the highest IF value, indicating that MgO may have great effect on inactivation of bacteria. Same phenomenon was observed in previous research [22], despite the experimental condition being a dust explosion in close bomb instead of an open air-acetylene flame with Mg particles injected. For biocidal materials with iodine, controversially, release of Iodine likely did little effect on inactivation rate.…”
Section: Biocidal Efficiency Of Mg-based Biocidal Materialssupporting
confidence: 86%
See 2 more Smart Citations
“…As-received Mg unexpectedly had the highest IF value, indicating that MgO may have great effect on inactivation of bacteria. Same phenomenon was observed in previous research [22], despite the experimental condition being a dust explosion in close bomb instead of an open air-acetylene flame with Mg particles injected. For biocidal materials with iodine, controversially, release of Iodine likely did little effect on inactivation rate.…”
Section: Biocidal Efficiency Of Mg-based Biocidal Materialssupporting
confidence: 86%
“…Of these materials, thermites with calcium iodate as an oxidizer have been well-studied [19][20][21]. In particular, MgÀ Ca(IO 3 ) 2 raised interest since combustion products of Mg have a very effective biocidal effect in sub-second exposures [20,22]. Previous research showed that iodine could be mechanochemically stabilized in metal powders, and can be used in Ca(IO 3 ) 2 -based thermites to increase iodine concentration [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combustion products showed biocidal action against spores of Bacillus thuringiensis giving an inactivation factor close to that obtained by typical iodinated composites such as Al•I 2 and Al•B•I 2 . In another analogous study relying upon similar preparation techniques, the biocidal properties of an elemental Mg and Mg•S composite were measured and compared [143]. The authors observed the existence of a biocidal effect of MgO, produced by the combustion of elemental Mg powder, which did not differ significantly from that typical of burnt Mg•S composite particles, likewise forming MgO.…”
Section: Non-halogenated Biocidal Thermitesmentioning
confidence: 99%
“…Nanothermites are mixtures of nanosized reactants, which are stable under moderate conditions and capable of interacting with each other with the release of large amounts of chemical energy after activation by a triggering stimulus (thermal, mechanical, or electrical). Much research in nanothermites has focused on Al-based systems such as Al/Fe 2 O 3 , Al/MoO 3 , Al/CuO, and Al/Bi 2 O 3 due to their high energy density , and combustion performance tunability. , Al-based nanothermites have found applications for joining or welding, , tunable generators of biocidal agents, , actuation in initiators/detonators, and in single-use miniaturized microelectromechanical systems. A key parameter to high reactivity in nanothermites is intimate interfacial contact between the fuel (Al) and oxidizer. That is why various preparation methods have been employed to combine the aluminum fuel and oxidizer together in close proximity, including sputter deposition, arrested milling methods, electrosprays, sol–gel processing, and self-assembly. Interestingly, in Al/CuO fully dense materials such as composites prepared by arrested reactive milling and reactive multilayers, the exothermic redox reaction is restricted to condensed phase reactions at the CuO–Al interface, where an amorphous product Al 2 O 3 layer grows and the ignition temperature is reduced compared to other types of thermites to ∼850 K. , Recent studies also showed that the ignition temperature can be further decreased by adding micro- or nanovoids within the interfacial layer, which was unexpected.…”
Section: Introductionmentioning
confidence: 99%